What Happened to the Feminist Policy? A Feminist Foreign Policy Analysis of Sweden’s Former Feminist Foreign Policy - Selin,Axel (2024)
Sweden’s adoption of a feminist foreign policy in 2014 was the first of its kind, marking a significant shift in how it would conduct its foreign policy. Since then, the effect feminist foreign policies have on feminist discourse has been a growing field of study. This thesis adds to this by examining the relationship between actors, foreign policy, and feminist discourse. By combining feminist international relations theory, foreign policy analysis, and critical discourse analysis, the thesis analyses the annual declarations of three Swedish foreign ministers - Margot Wallström, Ann Linde, and Tobias Billström. Together with the theoretical framework, central themes of agency-structure and change-continuity are used to uncover the shifts in feminist discourse over time. The thesis concludes that through a complex interaction of agency and structure, Margot Wallström and Ann Linde broadened what feminist discourse entailed, whilst Tobias Billström contested it.
Keywords: feminist foreign policy; gender; discourse analysis; international relations